2016
DOI: 10.1523/jneurosci.0226-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Hearing Loss Has Long-Lasting Structural and Molecular Effects on Presynaptic and Postsynaptic Structures of Auditory Nerve Synapses in the Cochlear Nucleus

Abstract: Sound deprivation by conductive hearing loss increases hearing thresholds, but little is known about the response of the auditory brainstem during and after conductive hearing loss. Here, we show in young adult rats that 10 d of monaural conductive hearing loss (i.e., earplugging) leads to hearing deficits that persist after sound levels are restored. Hearing thresholds in response to clicks and frequencies higher than 8 kHz remain increased after a 10 d recovery period. Neural output from the cochlear nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 84 publications
10
61
0
Order By: Relevance
“…These AMPAR complexes contain very little GluA2 and are mainly composed of GluA3 and GluA4 subunits (Gardner et al, 1999; Petralia et al, 2000; Wang et al, 1998). Previously we reported that transient sound reduction leads to an increase of GluA3 immunogold labeling at the postsynaptic density of AN-BC synapses (Clarkson et al, 2016; Whiting et al, 2009). Based on these observations, we hypothesized that GluA3 is involved in normal auditory processing and in experience-related changes in the auditory brainstem.…”
Section: Introductionmentioning
confidence: 93%
“…These AMPAR complexes contain very little GluA2 and are mainly composed of GluA3 and GluA4 subunits (Gardner et al, 1999; Petralia et al, 2000; Wang et al, 1998). Previously we reported that transient sound reduction leads to an increase of GluA3 immunogold labeling at the postsynaptic density of AN-BC synapses (Clarkson et al, 2016; Whiting et al, 2009). Based on these observations, we hypothesized that GluA3 is involved in normal auditory processing and in experience-related changes in the auditory brainstem.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, it was shown that prolonged visual deprivation increases visually evoked V1 responses during the visual critical period 10 . However, evidence for homeostatic synaptic scaling in primary auditory cortex and its effects on cortical responsiveness following auditory deprivation is rare.Previously, two models for induction of an auditory deprivation have been used, sensorineural hearing loss (SNHL) [11][12][13] and conductive hearing loss (CHL) [14][15][16][17] . Whereas SNHL removes both sensory evoked activity and spontaneous activity arising from the organ of Corti 3 , CHL only reduces sound transmission to the inner ear without affecting the cochlea, reflecting a milder form of hearing loss 11 .…”
mentioning
confidence: 99%
“…Previously, two models for induction of an auditory deprivation have been used, sensorineural hearing loss (SNHL) [11][12][13] and conductive hearing loss (CHL) [14][15][16][17] . Whereas SNHL removes both sensory evoked activity and spontaneous activity arising from the organ of Corti 3 , CHL only reduces sound transmission to the inner ear without affecting the cochlea, reflecting a milder form of hearing loss 11 .…”
mentioning
confidence: 99%
See 2 more Smart Citations